The Financial Stability, Monitoring, and Replacement Directors on Fraudulent Financial Reporting - Mutia Sari; Ratna Mappanyukki (Politeknik Caltex Riau, 2022)
An issue of concern is fraudulent financial reporting, which has the potential to cause significant economic losses to investors and the government, as well as a loss of investor trust because it may lead to investors making poor investment decisions. With fraudulent financial reporting as a dependent variable, this study's primary goal is to investigate the empirical financial stability, monitoring, and replacement of company directors, all of which are used as proxies for the pressure, opportunity, and capability elements of fraudulent financial reporting. The banking industry makes up the majority of the study's participants. Purposive sampling was used to select 123 companies for the research sample; panel data regression was used as the statistical method, and EViews 10 was used as the statistical processing software. There was a correlation between fraudulent financial reporting and monitoring in this study, but not between financial stability and the replacement of board members of directors.